LOT-G3: PLASMA LAMP, OZONATOR AND CW TRANSMITTER - Gobato, Ricardo (2016)
The LOT-G3 is designed to be a versatile equipment that perform several simple experiments for use in helping the physics classes for high school. Easy construction, low cost, using easily accessible materials. Its construction involves simple practices and knowledge of electromagnetism. It has the function of a plasma globe to demonstrate the ionization of a low pressure gas, as well as the formation of magnetic field. Can be used as sanitizer closed environments such as automotive vehicles in ozonator function, demonstrating the ionization of oxygen in the atmosphere, producing ozone, essential to life on earth. And as a sparks transmitter, low power, low frequency modulated continuous wave in (CW), for signals in Morse code. Therefore the equipment here called LOT-G3, has three functions: a plasma lamp, ozonator and CW transmitter.